Using the Equivalence Paradigm to Increase the Correspondence of Vocalizations by Children with Cochlear Implant in Picture Naming and Reading - Anastacio-Pessan, Fernanda Luz; Moreira Almeida-Verdu, Ana Claudia [UNESP]; Bevilacqua, Maria Cecilia; Souza, Deisy das Gracas de (Univ Federal Rio Grande Sul, 2015)
The present study investigated the effects of strengthening equivalence relations between spoken words, printed words, and pictures to improve the correspondence between vocalizations in picture naming and in reading tasks in children with cochlear implant. Before the study, the children pronounced words better while reading than while naming pictures. The procedure taught two sets of three relations between dictated words and pictures, between the same dictated words and printed words, and between dictated and printed syllables. Periodic probes evaluated the experimental effects according to a multiple baseline design between stimulus sets. Picture naming and reading of all six words were probed before and after teaching each type of relationship and testing for class formation for each stimulus set. Picture naming progressively improved for five of six participants across teaching and probes with Stimulus Set 1, and for all participants across Stimulus Set 2. Reading scores, initially high, also reached perfect or near perfect accuracy. The results extend previous findings on the potential of procedures based on the stimulus equivalence paradigm for improving speech and listening comprehension of children with cochlear implant.
Keywords: Picture naming; reading; equivalence relations; hearing loss; cochlear implant